Taxonomic characterization, morphological variability, and geographic patterns of Juniperus turbinata Guss. in Algeria - Elmir, Merouane; Beghami, Yassine; Mazur, Małgorzata (Biodiversity: Research and Conservation, 2024)
A biometric study of cones, seeds, needles, and branchlets was conducted in 15 natural populations of Juniperus turbinata Guss. within its Algerian range. Each population was represented by 20-30 individuals. A total of 386 individuals were examined to evaluate inter- and intraspecific variation, and its geographic patterns, confirming the status of J. turbinata in Algerian populations. Maritime and mainland (Atlas Mountains) populations differed significantly. Cones in the seaside areas tended to be longer and more turbinate, with fewer seeds (mean 4.80) and leaves on the terminal 5-mm section of lateral branchlets (mean 27.87), compared to those from the Atlas, with 5.75 seeds and 29.00 leaves on average. The Aurès Mountain populations had more leaves than other scale-like junipers and other species of the Cupressaceae. Furthermore, maritime populations stood out for having the most turbinated cones among recorded Juniperus phoenicea s.l. populations. Costal populations were more related to those located on oriental Mediterranean shores, while Atlas Mountain populations seemed to be related to Moroccan Atlas ones. A negative gradient of leaf number from east to west was identified in the Atlas group, extending into Morocco. The distinct separation between the 2 geographic patterns supports the hypothesis of migration of J. turbinata along 2 routes and relaunches the proposal of possible varieties within the group.